2012
DOI: 10.1080/13501763.2012.632150
|View full text |Cite
|
Sign up to set email alerts
|

With Luxembourg in mind … the remaking of national policies in the face of ECJ jurisprudence

Abstract: This contribution analyses EU member state political responses to ECJ challenges. Faced with high consensus requirements at the European level, member states often have to respond unilaterally and explore how to pursue autonomous regulatory goals in 'ECJ-proof' ways.Based on an actor-centered institutionalist framework, member states' domestic responses to one prominent series of ECJ judgments (Laval, Rüffert, Commission vs Luxembourg) are traced empirically. By anticipating potential legal challenges through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 24 publications
(7 reference statements)
2
74
0
1
Order By: Relevance
“…Jensen and Spoon (2011) showed the partisanship of governments had a crucial influence on member states' compliance with the greenhouse gas reduction targets agreed among EU member states to implement the Kyoto Protocol. Additional evidence on the relevance of party politics was presented by studies on member states' reactions to ECJ case law in the fields of healthcare, trade union rights, and citizenship (Obermaier 2009;Sack 2012;Blauberger 2012;Schmidt 2014).…”
Section: Domestic Factors Related To Member States' Willingness To Comentioning
confidence: 99%
“…Jensen and Spoon (2011) showed the partisanship of governments had a crucial influence on member states' compliance with the greenhouse gas reduction targets agreed among EU member states to implement the Kyoto Protocol. Additional evidence on the relevance of party politics was presented by studies on member states' reactions to ECJ case law in the fields of healthcare, trade union rights, and citizenship (Obermaier 2009;Sack 2012;Blauberger 2012;Schmidt 2014).…”
Section: Domestic Factors Related To Member States' Willingness To Comentioning
confidence: 99%
“…First, mere neglect is often unsustainable or even counter-productive for limiting the domestic impact of the Court's case law. Rather, member state legislatures may have to engage in systematic reforms precisely to shield domestic policies from further judicial intervention (Blauberger 2012). The underlying political rationale in these instances, then, is that 'it is better to define than to be defined' (Martinsen 2005(Martinsen : 1049.…”
Section: False Expectations Vs Real Impactmentioning
confidence: 99%
“…By achieving this goal, Blauberger observed that 'the ECJ triggers broader reforms at the national level.' 100 In the case of the access rights and transparency regime, the CJEU jurisprudence has provided many precedents that deal with the relationship between national and union policies and legislation (IFAW, the Donau Chemie).…”
Section: Preliminary Implications and Counterargumentsmentioning
confidence: 99%